2017
DOI: 10.1080/14786435.2017.1408967
|View full text |Cite
|
Sign up to set email alerts
|

Bounds on size-dependent behaviour of composites

Abstract: Computational homogenisation is a powerful strategy to predict the effective behaviour of heterogeneous materials. While computational homogenisation cannot exactly compute the effective parameters, it can provide bounds on the overall material response. Thus, central to computational homogenisation is the existence of bounds. Classical firstorder computational homogenisation cannot capture size effects. Recently, it has been shown that size effects can be retrieved via accounting for elastic coherent interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…The recently introduced novel weak PBC [46] and other advanced techniques still belong to one of the three classical types of BC from this perspective. It is well-known that the DBC overestimate stresses, while the TBC underestimate them [6,44,45,48,55,56]. The most reliable results even in case of random materials are obtained using the PBC, which is however often criticized in literature since random samples are not periodic.…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently introduced novel weak PBC [46] and other advanced techniques still belong to one of the three classical types of BC from this perspective. It is well-known that the DBC overestimate stresses, while the TBC underestimate them [6,44,45,48,55,56]. The most reliable results even in case of random materials are obtained using the PBC, which is however often criticized in literature since random samples are not periodic.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Firstly, we need to design a suitable model of the microstructure and transfer macroscopic loads and deformations to the microscale. This is done using the Hill-Mandel [14,23,44,45,54] condition which states that the virtual work performed by microscopic stresses at microscopic deformation gradients must be equal to the virtual work performed by macroscopic (homogenized) stresses at macroscopic (homogenized) deformation gradients. The second step is to simulate the response of the micromodel.…”
Section: Introductionmentioning
confidence: 99%
“…The use of periodic boundary conditions for the statistically similar (substitute) model is motivated by a number of studies demonstrating that the periodic boundary conditions are the most reliable and converge faster than Dirichlet and Neumann boundary conditions . They are often used even if the model is not periodic, because Dirichlet and Neumann boundary conditions always give an overestimation and an underestimation for the stress in computational homogenization. Moreover, the simple comparison of the homogenized stresses in periodic composites modeled with only one inclusion in the unit cell and composites with a random microstructure, performed in the work of Zabihyan et al, demonstrated close homogenized stress values in both models.…”
Section: Stochastic Rvementioning
confidence: 99%
“…A major shortcoming of the classical computational homogenization is that it fails to account for size-dependent material behavior, often referred to as size effects. On the other hand, the size effects in composites are essentially attributed to surface [31] and interface effects [32,33] leading to significant properties of nano-materials due to their pronounced area-to-volume ratio, see [34][35][36][37][38] among others. Therefore, it is important to extend the computational homogenization method to account for the interfaces between the constituents of a micro-structure so as to capture the size effects.…”
Section: Introductionmentioning
confidence: 99%